Unraveling Chinese talk about emotion - Yik, Michelle; Chen, Celia Z. (Frontiers in Psychology, 2023)
Research in cross-cultural psychiatry has asserted that Chinese people have a higher tendency to report somatic symptoms of their psychological distress than people with a European ethnic background. However, recent studies have reached inconsistent conclusions and most have confounded language use with culture in their study designs. Focusing on the varying degrees of orientation to Chinese culture, the present study examined the words freely listed by two Chinese groups of university students (mainland Chinese and Hong Kong Chinese) when describing their illness experience. Words were categorized into somatic, emotion, and somatic–emotion clusters. The enculturated mainland Chinese participants—who reported greater Chinese cultural identity—used significantly more emotion words but fewer somatic–emotion words than the Hong Kong Chinese participants. No group differences were found in somatic words. In contrast to previous findings, the current study failed to find support for the relationship between culture and somatic symptom reporting when controlling for language use. Overall, the Chinese participants were more willing to talk about their emotions than their somatic symptoms in an anonymous survey.